2013
DOI: 10.1002/lary.23907
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels ofTNF‐α,IL‐10, andIL‐12in idiopathic sudden sensorineural hearing loss

Abstract: IL-10 and IL-12 may not play a critical role in idiopathic sudden sensorineural hearing loss. But our data supports the role of TNF-α in the pathophysiology of idiopathic sudden sensorineural hearing loss, and TNF-α receptor blockers may have benefits in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 33 publications
1
55
2
1
Order By: Relevance
“…Our result supports the study by Demirhan et al [2013] which showed that TNFα posttreatment values are elevated in the treatment nonresponders and complies with both clinical trials and case reports in the literature that favor the use of TNFα inhibitors in the treatment of ISSNHL [Staecker and Lefebvre, 2002;Satoh et al, 2002Satoh et al, , 2003Van Wijk et al, 2006;Demirhan et al, 2013]. With the exception of our study and the one recently published by Demirhan et al, the variation of TNFα expression has not been evaluated in other research protocols.…”
Section: Discussionsupporting
confidence: 73%
“…Our result supports the study by Demirhan et al [2013] which showed that TNFα posttreatment values are elevated in the treatment nonresponders and complies with both clinical trials and case reports in the literature that favor the use of TNFα inhibitors in the treatment of ISSNHL [Staecker and Lefebvre, 2002;Satoh et al, 2002Satoh et al, , 2003Van Wijk et al, 2006;Demirhan et al, 2013]. With the exception of our study and the one recently published by Demirhan et al, the variation of TNFα expression has not been evaluated in other research protocols.…”
Section: Discussionsupporting
confidence: 73%
“…Generally, it is an increase in TNF-α signaling, either secondary to disease or via pharmacological manipulation, that will cause loss of hair cells or auditory function, while blocking TNF-α affords protection in both human and animal models. Patients with idiopathic sensorineural hearing loss who did not respond to drug treatment maintained higher blood levels of TNF-α than positive responders (Demirhan et al 2013). Autoimmune sensorineural hearing loss was also attenuated by TNF-α blockers in a prospective pilot study (van Wijk et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Masuda et al [9] reported that the increase in neutrophil count was correlated with a poor prognosis for SSNHL patients. Studies performed with inflammatory cytokines, like TNF alpha, interleukin 6, and interleukin 10, demonstrated that these cytokines were not correlated with SSNHL [16,17] . Neutrophil-to-lymphocyte ratio (NLR) is calculated by dividing the neutrophil count obtained from the CBC analysis by the lymphocyte count.…”
Section: Discussionmentioning
confidence: 99%